Adolescent mental health in the context of adversity : evidence from a longitudinal intervention study in Khayelitsha, South Africa - Du Toit, Stefani (Stellenbosch : Stellenbosch University, 2023)
Thesis (PhD)--Stellenbosch University, 2023.